2023
DOI: 10.19045/bspab.2023.120074
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on cotton planting date and planting density using modelling techniques: Review

Abstract: Climate change effects on cotton planting date and planting density using modelling techniques: Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…An imbalanced nutrient profile can affect cotton yield even if phosphorus levels are sufficient (Sekhon and Singh, 2013;Iqbal et al, 2020;Solangi et al, 2023). The interaction between sowing dates and phosphorus levels is not significant for plant height, suggesting that the effect of sowing dates on plant height is consistent across different phosphorus levels, and vice versa (Iqbal et al, 2023). Similarly, the interaction is not significant for the number of leaves per cotton plant, implying that the influence of sowing dates on the number of leaves and the influence of phosphorus levels on the number of leaves are consistent and do not interact significantly (Khan et al, 2019).…”
Section: Influence Of Sowing Dates and Phosphorus Levels On Cotton Pe...mentioning
confidence: 96%
“…An imbalanced nutrient profile can affect cotton yield even if phosphorus levels are sufficient (Sekhon and Singh, 2013;Iqbal et al, 2020;Solangi et al, 2023). The interaction between sowing dates and phosphorus levels is not significant for plant height, suggesting that the effect of sowing dates on plant height is consistent across different phosphorus levels, and vice versa (Iqbal et al, 2023). Similarly, the interaction is not significant for the number of leaves per cotton plant, implying that the influence of sowing dates on the number of leaves and the influence of phosphorus levels on the number of leaves are consistent and do not interact significantly (Khan et al, 2019).…”
Section: Influence Of Sowing Dates and Phosphorus Levels On Cotton Pe...mentioning
confidence: 96%
“…Mahdi et al (2019) reported that early planting (1 st April) is suitable for the Egyptian cotton genotypes, especially Giza 95, through the appropriate climatic window that corresponds to the different growth stages to produce higher production by creating a good equilibrium between vegetative growth and fruiting ability and maximizing the activity utilization of heat thermal units. The most important and most manageable factor for cotton yield is the optimal time to plant the new variety in the area (Iqbal et al, 2023). The environment change affects agricultural production by affecting managing practices like planting time.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes around 0.6% to GDP and 2.4% of the value added in Agriculture (GoP, 2021(GoP, -2022. The most significant and manageable factor for cotton crop is optimum planting time for new cultivar in region (Jaffar, et al, 2023). The environment change is affecting the Agricultural production by affecting on managing practices such as planting time.…”
Section: Introductionmentioning
confidence: 99%